WYZNACZNIKI PROFESJONALIZMU NAUCZYCIELA – DYSKUSJA GLOTTODYDAKTYCZNA A POLITYKA I PRAKTYKA OŚWIATOWA - Jaworska, Mariola (Neofilolog, 2020)
The professionalism of a teacher is their competence, expertise, “knowledge of the craft”, but also the ability to meet high cognitive, operational and ethical standards. On the one hand, this is rooted in social and cultural expectations, related to the educational needs of society, but on the other it has a personality dimension, connected with the teacher’s individuality, which is evidenced in the specific relations they have with students. This article aims to analyse the determinants of the professionalism of the contemporary foreign language teacher found in recent glottodidactic discussion and compare these to the current educational policy and practice. It will present both theoretical approaches and the selected results of studies and reports on this topic.